2015
DOI: 10.3390/ijms161125983
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA Expression Status of Dopamine Receptor D2, Dopamine Receptor D3 and DARPP-32 in T Lymphocytes of Patients with Early Psychosis

Abstract: Peripheral blood lymphocytes are an attractive tool because there is accumulating evidence indicating that lymphocytes may be utilized as a biomarker in the field of psychiatric study as they could reveal the condition of cells distributed in the brain. Here, we measured the mRNA expression status of dopamine receptor D2 (DRD2), DRD3, and dopamine and cyclic adenosine 3′,5′-monophosphate regulated phosphoprotein-32 (DARPP-32) in T lymphocytes of patients with early psychosis by quantitative real-time polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
2
23
0
1
Order By: Relevance
“…Further, DRD3 expression correlated with the excitement factor on the PANSS in patients with schizophrenia/schizophreniform disorder. According to the authors, DRD3 mRNA levels can be used as a diagnostic marker to differentiate patients with early psychosis from healthy controls [ 237 ].…”
Section: Clinical Implications Of the Effects On The Dopaminergic mentioning
confidence: 99%
“…Further, DRD3 expression correlated with the excitement factor on the PANSS in patients with schizophrenia/schizophreniform disorder. According to the authors, DRD3 mRNA levels can be used as a diagnostic marker to differentiate patients with early psychosis from healthy controls [ 237 ].…”
Section: Clinical Implications Of the Effects On The Dopaminergic mentioning
confidence: 99%
“…Unfortunately, there are on this topic inconclusive reports as well. No change in DARPP-32 protein levels were found in schizophrenic prefrontal and cingulate cortex and T lymphocytes of elderly patients with schizophrenia [ 75 , 76 ]. Mutation analysis of DARPP-32 gene indicate that it is not a major susceptibility gene for schizophrenia [ 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding rs6280 polymorphism alone, a recent study demonstrated that levels of DRD3 mRNA on T lymphocytes were significantly different between controls and individuals with unspecified psychotic disorder and SCZ (Cui et al, 2015). Another study showed that there is an excess of the C allele and homozygotes for this allele in patients with tardive dyskinesia (an irreversible adverse effect of the antipsychotic medication) (Utsunomiya et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To try to understand the refractoriness of several drugs a pharmacogenetic approach has been used. Pharmacogenetics place genetic variation as a possible reason for the absence or poor response to adequate medication (Cui et al, 2015). Large-scale genomic association studies of SCZ identified 108 genetic loci associated with this disorder.…”
Section: Introductionmentioning
confidence: 99%